2015
DOI: 10.1002/14651858.cd006349.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty for osteoporotic vertebral compression fracture

Abstract: Based upon moderate quality evidence, our review does not support a role for vertebroplasty for treating osteoporotic vertebral fractures in routine practice. We found no demonstrable clinically important benefits compared with a sham procedure and subgroup analyses indicated that results did not differ according to duration of pain ≤ 6 weeks versus > 6 weeks. Sensitivity analyses confirmed that open trials comparing vertebroplasty with usual care are likely to have overestimated any benefit of vertebroplasty.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 90 publications
1
92
0
Order By: Relevance
“…For example, a recent (2015) HTA publication by the Cochrane Collaboration recommended against using VP to treat VCFs in routine clinical practice. 55 This recommendation disregarded 11 RCTs and 1 ''quasi RCT,'' classifying all non-placebo-controlled trials as having high risk of bias, and therefore based the conclusion against VP on only the 2 NEJM sham trials, which were classified as Level I rather than Level II data. This arbitrary classification and selective information culling is one example of how significant discrepancies can arise between HTA reviews and high-quality meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent (2015) HTA publication by the Cochrane Collaboration recommended against using VP to treat VCFs in routine clinical practice. 55 This recommendation disregarded 11 RCTs and 1 ''quasi RCT,'' classifying all non-placebo-controlled trials as having high risk of bias, and therefore based the conclusion against VP on only the 2 NEJM sham trials, which were classified as Level I rather than Level II data. This arbitrary classification and selective information culling is one example of how significant discrepancies can arise between HTA reviews and high-quality meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] The first Cochrane review for vertebroplasty was published in 2015. 22 This also detailed the review protocol which has not been updated and still applies to the more recent Cochrane review published in 2018. This included 21 trials and declared that high-to moderate-quality evidence suggested vertebroplasty provides no clinically important benefits with respect to pain, disability, QoL or treatment success after 1 month.…”
Section: Meta-analysesmentioning
confidence: 99%
“…In a Cochrane systematic review of 11 published RCTs undertaken in a various countries assessing the effects of vertebroplasty compared with either placebo in two trials, usual care in six trials, balloon or shield kyphoplasty in three trials [26], it was concluded that there was insufficient evidence supporting their efficacy in pain reduction and functional improvement, and therefore these percutaneous vertebral augmentation procedures should not be considered as a routine treatment for VCFs. Patients should be informed about the lack of high-quality evidence supporting benefit of PVP and its potential complications.…”
Section: Surgical Management Of Osteoporotic Vcfmentioning
confidence: 99%